Vocational Education and Skills Training in Traditional Islamic Schools in Southeast Asia (1975–2025) - Pamungkas, Alim Harun; Aryawan, Fatah Nasikh; Ramadani, Putra; Ramadhani, Rizki Putri; Fauzi, Handriva; Hendri, Sherlyane; Saputra, Anggi Firmanjaya (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
Traditional Islamic educational institutions have historically shaped religious and socio-cultural life in Southeast Asia, yet their contribution to vocational education and skills training has not been systematically synthesized. This study examines how vocational education has been conceptualized and implemented in traditional Islamic schools (pesantren, pondok, and madrasah) across Indonesia, Malaysia, Thailand, Brunei Darussalam, and Singapore from 1975 to 2025. Using a Systematic Literature Review (SLR) guided by PRISMA 2020, 2,099 records were identified in Scopus, of which 32 peer-reviewed studies met the inclusion criteria for analysis. The findings indicate three major patterns. First, vocational education in Islamic schools has evolved from informal life-skills transmission into more structured models, including entrepreneurship training, agricultural programs, TVET-aligned curricula, and hybrid digital initiatives. Second, significant cross-national variation exists: Indonesia (n = 18) and Malaysia (n = 7) show stronger institutional integration with national TVET systems, while Thailand (n = 3), Brunei (n = 2), and Singapore (n = 2) emphasize community-based or hybrid skill models. Third, vocational education is framed not only as employability enhancement but also as religious obligation and identity formation. Theoretically, the review demonstrates that vocational education in Islamic institutions functions simultaneously as an economic strategy, a capability-expanding process, and an identity-forming practice. These findings challenge state-centered conceptions of TVET and reposition Islamic schools as adaptive actors in regional skills ecosystems. Future research should incorporate comparative field studies, longitudinal institutional analysis, and multilingual databases to deepen empirical and contextual understanding.